Isolation of Nitrification-Denitrification Fungus for Removal of Ammonium-Nitrogen - Lv, Yongkang; Niu, Feilong; Liu, Yuxiang; Yang, Xiaohua (Asian Journal of Chemistry, 2014)
A filamentous fungus, which exhibited an ability to remove high-strength ammonium nitrogen and had nitrification-denitrification characteristics, was isolated from the activated sludge of a cokes wastewater treatment facility and named A60. It was provisionally identified as Fusarium sp, according to its colonial morphology, microscopic photos and 26S rDNA-ITS sequences analysis. In order to optimum its ammonium removal conditions, several experiments were designed at different carbon sources, nitrogen sources, C/N ratios (mol/mol) and pH. Under optimum conditions, an initial concentration of 450 mg/L NH4+-N was removed by 94.97 %, while total nitrogen was reduced by 88.35 %, however, with a few accumulation of hydroxylamine, nitrite and nitrate during nitrification process. Ammonium or the nitrification products such as hydroxylamine, nitrite and nitrate was used as the only source of nitrogen in aerobic denitrification experiment, respectively. The results indicated that all the kinds of nitrogen source could be utilized and converted to nitrogen gas (N2) about 35-45 %. A60 performed powerful simultaneous nitrification-denitrification ability.